Continental Reality Television and the Expansion of South African Capital - Jacobs, Sean (The Politics of Reality Television: Global Perspectives, 2010)
This chapter wants to argue two things: the ﬁrst part suggests that reality television in Africa – speciﬁcally the series Big Brother Africa, which completed its third season in November 2008 – has had profound impacts for identity politics, gender politics, and the politics of class on the continent. In fact, these are the issues most commonly illuminated by reality television and I wrote about these in a previously published article. The second part of the chapter moves into less explored territory. In that previous article, I brieﬂy discussed how speciﬁcally Big Brother Africa can illuminate the workings of globalization in Africa and, in particular, South Africa’s hegemonic role in that process. Here, I expand on my earlier argument by exploring that hegemony in the context of the growing Chinese presence in Africa. All economic and political indicators suggest that China’s growing investment in mining and infrastructure and its political clout relative to South Africa mean that it is destined to assume a place of prominence on the continent. But here I want to argue that if we want to understand how globalization plays out in Africa, we need to look beyond China’s military and economic expansion. For me, Big Brother Africa can help us make sense of these dynamic processes. South Africa has consistently remained the highest-ranking country in Africain terms of its “global competitiveness” as measured by the World Economic Forum. South Africa dominates regional markets in Southern Africa as well as remaining competitive in the rest of the continent against business rivals from United States and Europe. As it was under Apartheid, there is a close symbiosis between the continental aspirations and interests of the postapartheid state and that of South African business. The advent of democracy in 1994 has opened up African markets for South African business on an unprecedented scale. The South African state is very active on the African continent and keen to develop a leading role for itself. In fact, successive United States governments have viewed South Africa as a continental leader. For example, former President George W. Bush referred to former South African President Thabo Mbeki as his “point man in Africa.”4The South African government underwrites and actively promotes SouthAfrican business’s continental schemes through its “Proudly South African” campaign coordinated through an International Marketing Council situated in the Oﬃce of (the country’s) President since 2002, which links state nationalism with consumption. Separately a statutory Industrial Development Corporation (established in 1940) underwrites the business expansion of South African capital.
Num Pages: 17
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; Afrique du Sud (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Cultural Economy and Television in Jamaica and Ghana: #decolonization2point0 - Hickling Gordon, Deborah (Palgrave Pivot, 2020)
This book proposes contemporary decolonization as an approach to developing cultural economies in the Global South. This book represents the first critical examination and comparison of cultural and creative industries (CCI) and economy concepts in the Caribbean and Africa.
Keywords: 1-TV; 2-Approches sociologiques; 2-Méthodologie de recherche décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; Ghana (corpus analysé); Jamaïque (corpus analysé); Jamaïque (lieu de production du savoir); _Nettoyé

Culturaly Refigured: Assimilating Oedipus Rex into the Yoruba Mythical Universe Through Television Adaptation Processes - Ige, Segun (Television in Africa in the Digital Age, 2021)
Colonisation bequeathed classical education, among others, to the African continent. The post-colonial utility, function and status of such a knowledge system have been questioned and resisted, and African knowledgebased institutions are making efforts to decolonise such systems. The decolonial project has also impacted popular culture in the sense that African identity and self-presentation are being interrogated using various methods. Adaptations and productions of classical myths are implicated in this discourse. Implicated adaptations serve as platforms for allegorical cross-cultural conversation on shared experiences of a people group, perhaps of an earlier generation with the assumption of partial or absolute continuities. Continuity discourse is problematic when two cultures are implicated, particularly, when one is a colonial culture and the other colonised. The unity of discourse is either afﬁrmed, violated or reconstituted.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé; États-Unis (lieu de production du savoir)

South African Soapies: A “Rainbow Nation” Realized? - Burton, Nsenga K. (Watching While Black, 2012)
In the United States, daytime soap operas are often critiqued as escapist fantasies with narratives that provide leisure and pleasure for middle-class and stay-at-home mothers. The storylines typically involve forbidden sexual liaisons and business relationships, with physical and psychological behaviors that center on powerful families. One family unit usually represents “old money” while the other family represents “new money” or an upwardly mobile group with aspirations of power, status, and influence. The economic differences are usually the source of conflict between the families, around which all other social relationships develop. The temporal space expands and contracts to accommodate storylines, which
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Afrique (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; Afrique du Sud (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

“I Can be Who I Am When I Play Tekken 7”: E-sports Women Participants from the Islamic Republic of Pakistan - Hussain, Umer; Yu, Bo; Cunningham, George B.; Bennett, Gregg (Games and Culture, 2021)
Extant research on e-sports has focused on the growth and value of the phenomenon, fandom, and participant experiences. However, there is a paucity of e-sports scholarship detailing women’s experiences from marginalized communities living in various conservative Muslim countries. This shortage of literature remains despite different radical Islamic groups’ consistent demand for banning several online video games and the Muslim youth’s resistance to these calls. This study aimed to understand the motives and lived experiences of Muslim women e-sports participants from Gilgit-Baltistan, Pakistan. The authors collected data via observations of online video games and in-depth interviews. The study participants revealed that they use e-sports as a vehicle for an oppositional agency and personal freedom from the patriarchal system. The findings also suggest that participants are facing systematic marginalization and grave intrusion of post-colonization. The study contributes to the limited scholarship concerning Indian subcontinent Muslim women’s e-sports participation.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 3-Afrique (corpus analysé); 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Discours sur le colonialisme ; suivi de Discours sur la négritude - Césaire, Aimé (2015)
Comme naguère Jean-Jacques Rousseau dénonçait le scandale d'une société fondée sur l'inégalité, avec la même clarté, et un bonheur d'écriture que seule peut inspirer la passion du juste, Aimé Césaire prend ses distance par rapport au monde occidental et le juge. Ce discours est un acte d'accusation et de libération. Sont assignés quelques ténors de la civilisation blanche et de son idéologie mystifiante, l'Humanisme formel et froid. En pleine lumière sont exposées d'horribles réalités : la barbarie du colonisateur et le malheur du colonisé, le fait même de la colonisation qui n'est qu'une machine exploiteuse d'hommes et déshumanisante, une machine à détruire des civilisations qui étaient belles, dignes et fraternelles. C'est la première fois qu'avec cette force est proclamée, face à l'Occident, la valeur des cultures nègres. Mais la violence de la pureté du cri sont à la mesure d'une grande exigence, ce texte chaud, à chaque instant, témoigne du souci des hommes, d'une authentique universalité humaine. Il s'inscrit dans la lignée de ces textes majeurs qui ne cessent de réveiller en chacun de nous la générosité de la lucidité révolutionnaires. Le Discours sur le colonialisme est suivi du Discours sur la Négritude, qu'Aimé Césaire a prononcé à l'Université Internationale de Floride (Miami), en 1987.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé

Réécrire les mémoires et dénoncer l’histoire : l’art postcolonial - Meisel, Nina (AWARE : Archives of Women Artists, Research and Exhibitions, 2020)
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; _Nettoyé

Race-ing Art History: Critical Readings in Reace and Art History - Pinder, Kymberly N (Routledge, 2002)
This comprehensive anthology places issues of racial representation squarely on the canvas. Within these pages are representations of Nubians in ancient art, the great tradition of Westernmasters such as Manet and Picasso and contemporary work by lesser known artists.
OCLC: 804390860
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Afrique (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; 5-Créateur.rice autochtone; 5-Créateur.rice noir.e; 5-Créatrice; _Nettoyé

Femmes et violence de masse. - Myre, Nadia; Uzel, Jean-Philippe (Spirale, 2018)
"Si tous les groupes humains sont touchés par la violence à grande échelle, les femmes la subissent sous des formes spécifiques, comme en témoignent les assassinats systémiques des femmes et des filles autochtones en Amérique du Nord et en Amérique latine, ou encore les nombreux conflits armés (Syrie, Lybie, Birmanie, entre autres) dans lesquels le viol est érigé en arme de guerre. Les deux phénomènes peuvent d'ailleurs se recouper puisque l'un des tout premiers féminicides à avoir été qualifié et documenté comme tel en Amérique est celui ayant été perpétré contre les femmes mayas durant la guerre civile guatémaltèque au début des années 1980. Cependant, les femmes ne sont pas seulement les victimes de la violence de masse, puisqu'elles sont aussi les premières à témoigner et dénoncer pour faire barrage à cette violence. Ce numéro hors-série regroupe des articles et des projets visuels qui décrivent et analysent la violence de masse liée au genre. Il s'agit de réfléchir sur la manière de représenter cette violence et d'en témoigner, d'autant plus qu'elle est bien souvent rendue invisible et inaudible par le patriarcat, le colonialisme, les intérêts politiques en présence ou l'impéritie de l'État."
Section: 89 pages : illustrations en couleur ; 26 cm
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

El color de la razón: racismo epistemológico y razón imperial - Castro-Gómez, Santiago; Eze, Emmanuel Chukwudi; Henry, Paget (Ediciones del Signo, 2014)
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé

Manuel Zapata Olivella, le muntu africain et la décolonisation des imaginaires et des épistémologies en Amérique Latine - Akassi, Clément Animan (Matraga - Revista do Programa de Pós-Graduação em Letras da UERJ, 2019)
Ce travail vise à montrer deux choses. La première, c’est de saisir toute l’importance du tournant postcolonial/afro-décolonial dans la construction d’une contre-épistémologie propre au sujet culturel colonisé africain. En d’autres termes, pour le sujet colonisé, cette contre-épistémologie sert à décoloniser les imaginaires, à partir d’un questionnement de la colonialité de l’épistémologie et du savoir donnés pour universels par l’occident. La deuxième chose, c’est que ̶ à quelques mois de la commémoration du centenaire de la naissance du prolixe et polygraphe auteur africain-colombien Manuel Zapata Olivella (1920-2004) ̶ cet article puisse le situer à sa juste place. Celle d’un sujet culturel colonisé africain des Amériques dont l’abondante production culturelle et la pensée, portées et révolutionnées par le concept de Muntu africain, participent de la décolonisation des imaginaires et de l’épistémologie
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Afrique (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Créateur.rice PANDC; 5-Créateur.rice noir.e; _Nettoyé

Flora and Fauna Otherwise: Black and Brown Aesthetics of Relation in Firelei Báez and Wangechi Mutu - Alvarado, Leticia (Latin American and Latinx Visual Culture, 2019)
Pairing Dominican-born artist Firelei Báez with Kenyan-born artist Wangechi Mutu, this article meditates on relational black and brown aesthetic strategies by reading femme gestures performatively across individual works, as well as the exhibition spaces within which the artists draft practices of informed and resistant engagement. Working with both theories of brownness that emerge from Latinx studies as well as scholarship of the black radical tradition, the author follows a sense of shared aesthetic gestures in Báez and Mutu’s work toward an indictment of pervasive Global North racial epistemologies. Focusing on the performative gesture as the basis for relation, this article ultimately hones in on the chimeric figures—amalgamations of flora and fauna—that both artists deploy, arguing that these present a model for imagining an otherwise arrangement of the social.R Poniendo en diálogo a Firelei Báez, una artista nacida en República Dominicana, con Wangechi Mutu, que nació en Kenia, este artículo invita a una meditación sobre las estrategias estéticas relacionales negras y morenas mediante una lectura en clave performativa de gestos femeninos en obras individuales y en aquellos espacios de exposición en que las artistas elaboran prácticas de participación política informada y de resistencia. Trabajando tanto con las teorías de lo moreno (brownness) que emergen de los estudios Latinx como con el trabajo académico de la tradición radical negra, la autora rastrea gestos estéticos presentes tanto en el trabajo de Báez como en el de Mutu para denunciar las omnipresentes epistemologías raciales del norte global. Centrándose en el gesto performativo como la base de la relación, este artículo se enfoca en última instancia en las figuras quiméricas – amalgamaciones de flora y fauna – que ambas artistas despliegan en su trabajo para sostener que estas presentan un modelo para imaginar otra manera de organizar lo social.
Keywords: 1-Histoire de l'art; 2-Analyses formalistes; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; _Nettoyé

Postcolonial Modernism: Art and Decolonization in Twentieth-Century Nigeria - Okeke-Agulu, Chika (Duke University Press, 2015)
Written by one of the foremost scholars of African art and featuring more than 125 color images, Postcolonial Modernism chronicles the emergence of artistic modernism in Nigeria in the heady years surrounding political independence in 1960.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Créateur.rice noir.e; 5-Identités diasporiques; _Nettoyé

Black Art: Ancestral Legacy : The African Impulse in African-American Art. - Dallas Museum of Art (Dallas Museum of Art, 1990)
For the first time, a major exhibition examines the impact of African culture on black artists, both trained and self-taught, in a stunning range of 157 works which are variously bold, witty, historical, and mysterious. 49 biographical outlines; 320 illustrations, 170 in full color.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 3-Afrique (corpus analysé); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Créateur.rice PANDC; 5-Créateur.rice noir.e; _Nettoyé

Video Games and the Global South - Penix-Tadsen, Phillip (ETC Press, 2019)
Redefines games and game culture from south to north, analyzing the social impact of video games, the growth of game development and the vitality of game cultures across Africa, the Middle East, Central and South America, the Indian subcontinent, Oceania and Asia.
OCLC: 1104212185
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Humanités numériques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Video Games Around the World - Wolf, Mark J. P. (MIT Press, 2015)
Video games have become a global industry, and their history spans dozens of national industries where foreign imports compete with domestic productions, legitimate industry contends with piracy, and national identity faces the global marketplace. This volume describes video game history and culture across every continent, with essays covering areas as disparate and far-flung as Argentina and Thailand, Hungary and Indonesia, Iran and Ireland.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Black Europe Body Politics: Towards an Afropean Decolonial Aesthetics - Lockward, Alanna (Social Text Online, 2013)
The conceptualization of decolonial aesthetics is fairly recent, however its points of departure — the epistemic shifts that have been challenging coloniality in the artistic and cultural practices of the Global South — are as old as the colonial system. The defiance of colonialism in Vodou dance and rituals, which in Haiti ultimately led to the first successful enslaved people’s revolution, is a splendid case in point.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé